Health of people with selected citizenships: results of the study GEDA Fokus - Susanne Bartig; Carmen Koschollek; Marleen Bug; Miriam Blume; Katja Kajikhina; Julia Geerlings; Anne Starker; Ulfert Hapke; Alexander Rommel; Claudia Hövener (Journal of Health Monitoring, 2023)
Background: The health situation of people with a history of migration is influenced by a variety of factors. This article provides an overview of the health of people with selected citizenships using various indicators. Methods: The analyses are based on the survey ‘German Health Update: Fokus (GEDA Fokus)’, which was conducted from November 2021 to May 2022 among people with Croatian, Italian, Polish, Syrian and Turkish citizenship. The prevalence for each health outcome is presented and differentiated by sociodemographic and migration-related characteristics. Poisson regressions were performed to identify relevant factors influencing health situation. Results: Self-assessed general health, the presence of depressive symptoms, prevalence of current smoking and the utilisation of general and specialist healthcare differed according to various factors considered here. In addition to sociodemographic determinants, the sense of belonging to society in Germany and self-reported experiences of discrimination were particularly associated with health outcomes. Conclusions: This article highlights the heterogeneity of the health situation of people with a history of migration and points to the need for further analyses to identify the reasons for health inequalities.